I Am Hip-Hop : Conversations on the Music and Culture. - Rausch, Andrew J. (Rowman & Littlefield Pub. Group, 2011)
"What is Hip-Hop?" In order to answer this question, author Andrew J. Rausch interviewed 24 individuals whose creative expressions are intimately associated with the world of hip-hop music and culture. Those interviewed include emcees, DJs, producers, graffiti artists, poets, and journalists. Topics of these conversations cover the careers of each of these people and their contributions/affiliations with hip-hop, as well as their views on different trends within the music. Intended as a celebration of hip-hop music and culture, this collection of interviews ranges from the up-and-coming (Akro.